2020
DOI: 10.1302/0301-620x.102b5.bjj-2019-1496.r1
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of concentricity after closed reduction in developmental dysplasia of the hip

Abstract: Aims The goal of closed reduction (CR) in the treatment of developmental dysplasia of the hip (DDH) is to achieve and maintain concentricity of the femoral head in the acetabulum. However, concentric reduction is not immediately attainable in all hips and it remains controversial to what degree a non-concentric reduction is acceptable. This prospective study is aimed at investigating the dynamic evolution of the hip joint space after CR in DDH using MRI. Methods A consecutive series of patients with DDH who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…Talathi et al, 4 reviewing 30 hips treated by CR and spica casting, reported that femoral head position in the acetabulum improved for an average of three weeks, ranging from 13 to 46 days, after CR. A prospective study of 35 hips by Zhou et al 11 also demonstrated that concentricity of the femoral head dramatically improved between immediately and six months after CR and spica casting. More recently, Meng et al 21 revealed that the abnormal labrum-cartilage complex gradually returned to normal shape with the gradual inward displacement of the femoral head in a spica cast for four to six months after CR in 63 hips and thus concluded that it was unnecessary to deal with the abnormal structures at the time of reduction.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Talathi et al, 4 reviewing 30 hips treated by CR and spica casting, reported that femoral head position in the acetabulum improved for an average of three weeks, ranging from 13 to 46 days, after CR. A prospective study of 35 hips by Zhou et al 11 also demonstrated that concentricity of the femoral head dramatically improved between immediately and six months after CR and spica casting. More recently, Meng et al 21 revealed that the abnormal labrum-cartilage complex gradually returned to normal shape with the gradual inward displacement of the femoral head in a spica cast for four to six months after CR in 63 hips and thus concluded that it was unnecessary to deal with the abnormal structures at the time of reduction.…”
Section: Discussionmentioning
confidence: 91%
“… 4 , 9 , 10 Recently, a prospective MRI study quantitatively demonstrated the docking phenomenon following CR and revealed that inverted labrum at the time of CR delayed concentric reduction and acetabular remodelling. 11 To date, however, no previous study using MRI has elucidated the docking phenomenon following GR using traction and its relation to subsequent acetabular development. Assessment of the natural course of acetabular development following reduction requires observation without surgery until skeletal maturity, but in actual clinical practice, if acetabular dysplasia does not show sufficient spontaneous correction by the age of five to seven years, the operative management by a pelvic osteotomy has been indicated for minimizing the risk of early-onset hip osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, even after achieving a safe and stable closed reduction, limbus inversion remains a common phenomenon. Previous clinical observations showed that only 13.3% of the inverted limbus cases turned to eversion after closed reduction; the remaining cases saw the limbus embedded between the femoral head and the acetabulum, resulting in an increased joint space after reduction 6 . However, the current understanding of the outcome of the inverted limbus with DDH after closed reduction is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, 6 we performed serial MRI follow‐up observations of DDH patients who had undergone closed reductions. We found that 2 years after the procedure, the inverted limbus was still not completely absorbed in 86.7% of the cases; instead, they had evolved into a thin layer of fibrous tissue embedded between the femoral head and acetabulum.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, accurate calculation of the length change caused by femoral varus and the actual truncation distance before operation can effectively evaluate the necessity of osteotomy, thereby reducing the risk of operation to children to some degree. Besides, an osteotomy that is too large will also increase the tension of the joint soft tissues in children, thus increasing the risk of postoperative dislocation (25). In this study, there were no significant differences in the measured and calculated distances between the central point of the femoral head and the medial point of the proximal end of the osteotomy, and there were no significant differences between the 2 in the measurement of the shortened lengths of the proximal femur, suggesting that accurate assessment of femoral length had important clinical value.…”
Section: Discussionmentioning
confidence: 99%